TEACHER MEDIATION AND THE PEDAGOGICAL USE OF AUDIOVISUAL MEDIA IN ELEMENTARY SCIENCE LEARNING - Aliya Marsya As-Syifa; Heru Subrata; Fiena Saadatul Ummah; Nur Aini; Rona Zuhriyyata Adnin; Annas Sholihin (Jurnal Tatsqif, 2026)
This study examines how elementary teachers mediate audiovisual media in science learning and how such mediation shapes pupils’ access to abstract and sequential scientific concepts. Using a qualitative descriptive multiple-case design, the study involved six Grade 4 and Grade 5 teachers from three public elementary schools in Surabaya, Indonesia. Data were collected through semi-structured teacher interviews, classroom observations, follow-up interviews, lesson documents, worksheets, media files, and assessment tasks. Thematic analysis generated four main findings. First, teachers commonly viewed audiovisual media as a means of visual explanation, although media use was not always organised as guided inquiry. Second, pupils’ learning difficulties were related not only to the availability of media, but also to their ability to connect visual processes, scientific language, and causal explanation. Third, teacher mediation shaped whether audiovisual media supported active conceptual engagement or remained passive viewing. Fourth, implementation constraints included pedagogical issues such as media selection, questioning strategies, worksheet design, preparation time, and assessment practice, alongside technical limitations. The study highlights the importance of teacher guidance, representational tasks, and assessment support in making audiovisual media pedagogically meaningful in elementary science classrooms